High Surface Area N‐Doped Carbon Fibers with Accessible Reaction Sites for All‐Solid‐State Lithium‐Sulfur Batteries. Issue 6 (1st December 2021) - Sun, Xiao; Li, Qiang; Cao, Daxian; Wang, Ying; Anderson, Alexander; Zhu, Hongli
Abstract: Porous carbon plays a significant role in all‐solid‐state lithium‐sulfur batteries (ASSLSBs) to enhance the electronic conductivity of sulfur. However, the conventional porous carbon used in cell with liquid electrolyte exhibits low efficiency in ASSLSBs because the immobile solid electrolyte (SE) cannot reach sulfur confined in the deep pores. The structure and distribution of pores in carbon highly impact the electrochemical performance of ASSLSBs. Herein, a N‐doped carbon fiber with micropores located only at the surface with an ultrahigh surface area of 1519 m 2 g –1 is designed. As the porous layer is only on the surface, the sulfur hosted in the pores can effectively contact SE; meanwhile the dense core provides excellent electrical conductivity. Therefore, this structurally designed carbon fiber enhances both electron and ion accessibilities, promotes charge transfer, and thus dramatically improves the reaction kinetic in the ASSLSBs and boosts sulfur utilization. Compared to the vapor grown carbon fibers, the ASSLSBs using PAN‐derived porous carbon fibers exhibit three times enhancement in the initial capacity of 1166 mAh g –1 at C/20. An exceedingly cycling stability of 710 mAh g –1 is maintained after 220 cycles at C/10, and satisfactory rate capability of 889 mAh g –1 at C/2 is achieved. Abstract : Herein, a N‐doped carbon fiber with a core‐shell structure and high surface area of 1519 m 2 g −1, is designed, through which the charge transfer and reaction kinetics improved in the all‐solid‐state lithium‐sulfur batteries. Compared to the vapor grown carbon fibers, this design achieves three times enhancement in the initial capacity of 1166 mAh g −1 at C/20.